Homoplasy as an Auxiliary Criterion for Species Delimitation - Angela Conti; Debora Casagrande Pierantoni; Vincent Robert; Gianluigi Cardinali; Laura Corte (Microorganisms, 2021)
Homoplasy is a sort of noise in phylogenetic reconstructions, due to the accumulation of backmutations, convergent evolution and horizontal gene transfer (HGT), which is considered the major trigger of homoplasy in microorganism for its massive presence. It is also known that homoplasy increases with the complexity of the tree with both real and simulated data. In this paper, we analyzed the variation of homoplasy with the two widely used taxonomic markers ITS and LSU in four taxonomic models characterized by differences in the intra-specific distances. An algorithm (HomoDist) was developed to analyze the homoplasy index (HI) variation upon addition of a single element (strain or species) in increasing distance from a starting element. This algorithm allows to follow changes of the consistency index (CI), complementary to the HI, with the increase of the number of taxa and with the increase of the distance among elements. Results show that homoplasy increases—as expected—with the number of taxa, but also as a function of the overall distance among species, often with an almost linear relationship between distance and HI. No HI change was observed in trees with few taxa spanning through short distances, indicating that this noise is not prohibitive in this context, although the analysis of the ratio between HI and distance can be recommended as a criterion for tree acceptance. The absence of large changes of the HI within the species, and its increase when new species are added by HomoDist, suggest that homoplasy variation can be used as an auxiliary test in distance-based species delimitation with any type of marker.